Profiling of metabolite produced Monascus purpureus FTC5391 in two different substrates using HPLC- PDA and GC-MS - Ajdari, Zahra; Abdul Manan, Musaalbakri; Bayat, Saadi; Dinarvand, Mojdeh; Abbasiliasi, Sahar; Mohamad, Rosfarizan; Ariff, Arbakariya (Faculty of Engineering, Universiti Putra Malaysia, 2012)
In modern pharmacology, about half of the useful drugs are derived from natural sources where drug discovery from nature is an attractive subject for researchers. Monascus spp. has the ability in producing a collection of useful secondary metabolite which can be applied in food, cosmetic and pharmaceutics. In this study, the potential of Monascus purpureus FTC5391 in producing metabolites in solid state and submerged cultivation was investigated. The ethanolic extraction of these fermented products was evaluated using HPLC-PDA and GCMS. The results showed that the profiling of metabolites produced by Monascus purpureus FTC5391 in two different types of cultivation employed different media was significantly varied. The number of metabolites detected in Hiroi-pd submerged and soybean solid state cultivation was 100 and 55 compounds respectively with 10% similarity. These results demonstrated that the types of substrate were greatly affected on the number and sort of metabolites produced by Monascus purpureus FTC5391. Biological diversity and its constituent chemical diversity have served as one of the strongest sources of bioprospecting which leads to the discovery of some of the most important bioactive molecules for mankind. Therefore, the use of different medium composition for the cultivation of microorganisms would give an extreme opportunity to achieve a broad range of metabolites with different bioactivities.